2006
DOI: 10.1152/physiolgenomics.00111.2006
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale transcriptional analysis of bovine embryo biopsies in relation to pregnancy success after transfer to recipients

Abstract: The purpose of this work is to address the relationship between transcriptional profile of embryos and the pregnancy success based on gene expression analysis of blastocyst biopsies taken prior to transfer to recipients. Biopsies (30-40% of the intact embryo) were taken from in vitro-produced day 7 blastocysts (n = 118), and 60-70% were transferred to recipients after reexpansion. Based on the success of pregnancy, biopsies were pooled in three groups (each 10 biopsies) namely: those resulting in no pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
200
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(223 citation statements)
references
References 81 publications
(84 reference statements)
13
200
1
5
Order By: Relevance
“…The PLAC8, an invasion specific gene, is more abundant in blastocysts resulting in calf delivery compared with those resulting in resorption (El-Sayed et al 2006), and in endometrium of pregnant as compared with non-pregnant cows (Galaviz-Hernandez et al 2003, Klein et al 2006. These findings suggest a potential role for PLAC8 in placental development and fetus-maternal interface.…”
Section: Development and Gene Expression In Parthenotesmentioning
confidence: 86%
See 3 more Smart Citations
“…The PLAC8, an invasion specific gene, is more abundant in blastocysts resulting in calf delivery compared with those resulting in resorption (El-Sayed et al 2006), and in endometrium of pregnant as compared with non-pregnant cows (Galaviz-Hernandez et al 2003, Klein et al 2006. These findings suggest a potential role for PLAC8 in placental development and fetus-maternal interface.…”
Section: Development and Gene Expression In Parthenotesmentioning
confidence: 86%
“…Inhibition of PTGS2 increases pregnancy rates after embryo transfer and lowers PGF2a release (Scenna et al 2005). Expression of PTGS2 is more abundant in blastocysts resulting in calf delivery compared with those resulting in resorption (El-Sayed et al 2006). In bovine, the PTGS2 protein localizes to the TE, while the ICM does not express PTGS2 (Charpigny et al 1997), suggesting that this gene is necessary for the elongation and subsequent implantation.…”
Section: Development and Gene Expression In Parthenotesmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have attempted to correlate the differences in mRNA abundance observed at the blastocyst stage, such as those outlined above, with the ability of the embryo to establish a pregnancy. One such study (El-Sayed et al 2006) addressed the relationship between transcriptional profile of embryos and the pregnancy success based on gene expression analysis of blastocyst biopsies taken prior to transfer to recipients. Microarray data analysis revealed a total of 52 differentially regulated genes between embryos resulting in a calf delivery versus those not resulting in a pregnancy.…”
Section: Understanding the Implications Of Culture-induced Changes Inmentioning
confidence: 99%